Operational Risk Management Analysis Using Enterprise Risk Management (ERM) at PT Petrokimia Gresik - Firdausy, Naura; Winarno, Sri Tjondro; Setiawan, Risqi Firdaus (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2025)
This research aims to overcome operational risks that may occur using the Enterprise Risk Management (ERM) approach. The approach used to implement Enterprise Risk Management (ERM) in this study is SNI ISO 31000: 2018. The process of designing risk management goes through the stages of risk identification, risk analysis, risk evaluation, and risk treatment; the method used in thisstudy is qualitative descriptive with quantitative additions. That means descriptive qualitative methods are used for each stage of completion except the risk level assessment stage. This analysis was carried out at PT Petrokimia Gresik, precisely in the Production Department III A part ZA II. The problem in this study is that several risks can hinder the ZA fertilizer production process. The results of the analysis that have been carried out are 10 operational risks, namely Communication mistakes by the employees, Work accidents,Performance / low-productivities by the employees, Mistakes in operating production tools, Unsuitable product quality with the requested specification quality, ZA fertilizer that is not on target, Flawed storage of ZA fertilizer, Low availability of raw materials, Production reports failure and Production tools disturbance. Of the 10 risks identified, there are 8 risks at a low level (low), 2 risks at amedium level (medium) and 1 risk at a high level (high). Efforts to treat risks in the low (low) and medium (medium) level categories are to accept or restrain the risk from increasing and provide additional treatment. Meanwhile, for high-level risks, preventive and mitigation strategies are carried out to reduce the possibility and impact of these risks by doing some area maintenance to renovate the savings storage. Also, clumping fertilizer will be consulted in the quality control section.